2020
DOI: 10.1038/s41598-020-60835-4
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength, dynapenia, and mental health in older Koreans

Abstract: This study examined associations between muscle strength and mental health among 2,652 elderly Koreans who participated in the 2015 and 2017 Korea National Health and Nutrition Examination Survey. We measured absolute handgrip strength and calculated handgrip strength relative to body mass index. Dynapenia criteria followed that of the Asian Working Group for Sarcopenia. Questionnaires were used to assess mental health indicators including suicidal ideation, depressed mood, and stress status. Among participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 32 publications
(30 reference statements)
4
36
0
Order By: Relevance
“…Several studies have reported that low grip strength is associated with depressive symptoms, in men and women, independent of age [ 18 , 19 , 20 , 21 , 22 , 23 ]. However, the association of grip strength and depressive symptoms in the presence of different chronic diseases has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that low grip strength is associated with depressive symptoms, in men and women, independent of age [ 18 , 19 , 20 , 21 , 22 , 23 ]. However, the association of grip strength and depressive symptoms in the presence of different chronic diseases has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Stress level and sleep duration have been reported to be associated with sarcopenia in previous studies. There was a negative association between grip strength and stress levels in older people [56]. There was also an association between sleep disturbance and sarcopenia in older patients with diabetes [57].…”
Section: Discussionmentioning
confidence: 92%
“…The possible range of scores is 5-35, with a score of 20 representing a neutral point on the scale. Scores between 5-9 indicate that a respondent is extremely dissatis ed with life, whereas scores between [31][32][33][34][35] indicate that a respondent is extremely satis ed. Euro Quality of Life Visual Analogue Scale (EQ-5D) was designed to measure health related quality of life.…”
Section: Data Collection and Assaysmentioning
confidence: 99%